The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1590/s1516-89132002000300007
|View full text |Cite
|
Sign up to set email alerts
|

Possible Associations between Bovine Growth Hormone Gene Polymorphism and Reproductive Traits

Abstract: The polymorphism of the bovine growth hormone gene (bGH) was studied in 211 Nellore pure breed males for association with reproductive traits. Scrotal circumference and testosterone concentrations were collected monthly from 10 until 16 months of age. Additionally, testicular growth rates were calculated. DNA was amplified by PCR and digested using Msp I and Hae III restriction enzymes. Every polymorphism presented two alleles. The predominant alleles were D (0.85) and F (0.98), respectively, and genotype EE -… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 21 publications
0
14
0
2
Order By: Relevance
“…Some of them include the bovine growth hormone (bGH), associated with carcass fat content and muscle yield, milk yield, and testicular development (Yao et al, 1996;Unanian et al, 2002); the receptor of bGH, associated with a large number of productive traits such as milk yield and composition (Viitala et al, 2006), feed consumption, and feed conversion efficiency (Banos et al, 2008); and the bGH releasing hormone associated with carcass traits (Cheong et al, 2006). From an interactive network, some of these candidate genes, although not directly related to a determined trait, can have an indirect physiological relationship leading to significant enhancement of a correlated response in another trait (Paredes-Sánchez et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Some of them include the bovine growth hormone (bGH), associated with carcass fat content and muscle yield, milk yield, and testicular development (Yao et al, 1996;Unanian et al, 2002); the receptor of bGH, associated with a large number of productive traits such as milk yield and composition (Viitala et al, 2006), feed consumption, and feed conversion efficiency (Banos et al, 2008); and the bGH releasing hormone associated with carcass traits (Cheong et al, 2006). From an interactive network, some of these candidate genes, although not directly related to a determined trait, can have an indirect physiological relationship leading to significant enhancement of a correlated response in another trait (Paredes-Sánchez et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In animal species with long generation intervals, including cattle, genetic research aimed at the improvement of yield traits using conventional selection methods can be challenging, costly, and time-consuming. However, the marker-assisted selection method, based on the use of conventional selection methods in combination with genetic markers known or considered to be associated with certain yield traits, overcomes these disadvantages (2).…”
Section: Introductionmentioning
confidence: 99%
“…The growth hormone is involved in multiple physiological processes, including the regulation of growth, development of the mammary glands, onset of lactation, glucogenesis, activation of lypolysis, and regulation of muscle development 6 . In view of the abovementioned effects of the growth hormone, both GH concentration and the allelic variations of the gene coding this hormone have drawn the attention of researchers.…”
Section: Introductionmentioning
confidence: 99%
“…In view of the abovementioned effects of the growth hormone, both GH concentration and the allelic variations of the gene coding this hormone have drawn the attention of researchers. It has been reported that, in cattle, the bGH gene is correlated with certain yield traits, in particular with milk yield and quality, growth 6 , carcass composition and quality 7 . In this context, it is considered that it could be of use as a candidate gene in animal improvement programmes targeted at increasing milk and meat yields 8 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation